Pengaruh Model Pembelajaran Pendidikan Matematika Realistik (PMR) terhadap Hasil Belajar Siswa pada Mata Pelajaran Matematika SD Negari 14 Kelapa - Erwin Maulana; Ramanata Disurya; Tanzimah Tanzimah (Journal on Education, 2024)
The formulation of the problem in this study is whether there is an effect of realistic mathematics education (PMR) learning model on student learning outcomes in Mathematics class III SD Negeri 14 Kelapa. The purpose of this study was to determine whether there is an effect of realistic mathematics education (PMR) learning model on student learning outcomes in Mathematics class III SD Negeri 14 Kelapa. The research population was all third grade students of SD Negeri 14 Kelapa which amounted to 44 students. The method used in this research is experimental. The techniques used were test and documentation techniques. Based on the learning outcomes test, it is known that the experimental class test results with the highest score of 100 and the lowest score of 60 averaged 84.09. While the control class test results with the highest score of 90 and the lowest score of 40 averaged 62.27. The calculation results obtained thitung ¬= 6.017 and ttabel = 1.682 significant level = 0.05. Means thitung > ttabel, then Ha is accepted. Shows that there is an effect of realistic mathematics education (PMR) learning model on student learning outcomes in mathematics subjects in grade III SD Negeri 14 Kelapa.